Dysplasia Epiphysealis Hemimelica - Ishaq, Ruqqayya; Sheikh, Ahmareen Khalid; Zaffar, Ghazal; Akhter, Samina (International Journal of Pathology, 2018)
Dysplasia epiphysealis hemimelica (DEH) is a developmental disorder with a very low incidence. It is characterized by overgrowth of bone and cartilage in one or more epiphyses. The usual presentation of disease is in a single limb and is hemimelic (involving either lateral or medial compartment). Lower extremities are more frequently affected. Here we present a case of a male patient at 2.5 years of age presenting with bilateral involvement of knee joints by DEH. The diagnosis was confirmed on both radiological and histopathological findings.